TRENDS IN THE USE OF INTERACTIVE MEDIA FOR MATHEMATICS LEARNING IN ELEMENTARY SCHOOLS: A LITERATURE REVIEW (2015–2025) - Putri Indah Sari; Endang Susilaningsih; Bambang Subali; Ellianawati Ellianawati (Universitas Majalengka, 2026)
Mathematics learning at the elementary level plays a crucial role in developing students’ logical, systematic, and critical thinking skills, yet it is still widely perceived as abstract and difficult, indicating the need for pedagogical innovation through digital technology integration. This study aims to systematically analyze trends in the use of interactive media in elementary school mathematics learning from 2015 to 2025, focusing on media types, pedagogical implementation strategies, and learning outcomes. Employing a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines, literature was collected from Crossref, Google Scholar, and Scopus databases, yielding 1,243 articles, of which 28 studies met the inclusion criteria for analysis. The findings reveal three dominant trends: pedagogical trends marked by a shift toward student-centered learning models such as Problem-Based Learning and Digital Game-Based Learning; technological trends characterized by the increasing use of interactive multimedia, educational games, Augmented Reality, and interactive digital worksheets (E-LKPD); and cognitive trends reflected in a stronger focus on students’ motivation, engagement, and higher-order thinking skills. This review also identifies a key research gap in the limited longitudinal and context-sensitive evaluation of interactive media effectiveness in elementary mathematics learning. The scientific contribution of this study lies in its integrative synthesis of a decade-long development of interactive media by systematically linking media types, instructional models, and learning outcomes, offering a more comprehensive analytical perspective than previous short-term or media-specific reviews.